NAC103 mutation alleviates DNA damage in an Arabidopsis thaliana mutant sensitive to excess boron - Sotta, Naoyuki; Sakamoto, Takuya; Kamiya, Takehiro; Tabata, Ryo; Yamaguchi, Katsushi; Shigenobu, Shuji; Yamada, Masashi; Hasebe, Mitsuyasu; Sawa, Shinichiro; Fujiwara, Toru (Frontiers in Plant Science, 2023)
Excess boron (B) is toxic to plants and thereby causes DNA damage and cell death in root meristems. However, the underlying mechanisms which link boron and DNA damage remain unclear. It has been reported that the rpt5a-6 mutant of the 26S proteasome is sensitive to excess boron, resulting in more frequent cell death in root meristem and reduced root elongation. In this study, we showed that a reduction in root growth in the rpt5a mutant in the presence of high boron levels is repressed by a mutation in NAC domain containing transcription factor NAC103, a substrate of the proteasome, which functions in the unfolded protein response pathway. The mutation in NAC103 alleviated excess-B-induced DNA damage and cell death in root meristems of the rpt5a mutant. Superoxide (O2−) staining with nitroblue tetrazolium revealed that boron stress causes O2− accumulation in root tips, which was higher in the rpt5a-6 mutant, whereas the accumulation was lower in the rpt5a-6 nac103-3 double mutant. Our work demonstrates the overall involvement of NAC103 in maintaining healthy root meristem under excess boron conditions in the absence of RPT5A proteasome subunit.